PENERAPAN MODEL KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) PADA PEMBELAJARAN IPA BIOLOGI UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI DAN HASIL BELAJAR SISWA KELAS VIII.2 SMP NEGERI 34 PEKANBARU TAHUN AJARAN 2019/2020 - Nurul Hasanah; Arnentis Arnentis; Imam Mahadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to improve communication skills and learning outcomes through the implementation of the Two Stay Two Stray (TSTS) type cooperatif model in biology science learning for class VIII.2 students of SMP Negeri 34 Pekanbaru. This research was conducted from February to March 2020. The sample of this study was 36 students. The type of research used is Classroom Action Research (CAR) which is carried out for 2 cycles each cycle with 3 meetings and I time UH. The instruments used are learning tools and data collection instruments. The parameters observed were written communication skills, oral communication skills, learning outcomes in the form of absorption, learning completeness, group rewards, and attitudes. The results of this study indicate that the average value of students’ written communication skills in the first cycle is 78,80 in the sufficient category and the second cycle increases to 87,45 in the good category. The average value of the absorption of students in the first cycle was 78,27 in the sufficient category and increased in the second cycle to 84 in the good category. Completeness of learning outcomes in the first cycle were 27 (75%) students who completed and in the second cycle increased by 34 (94,44%) students who completed. The average value of the attitude in the first cycle was 80,85 in the sufficient category and increased in the second cycle to 86,27 in the good category. The average value of oral communication skills in the first cycle was 79,19 in the sufficient category and increased in the second cycle to 86,56 in the category. Based on the results of the study, it can be concluded that the implementation of the Two Stay Two Stray (TSTS) type cooperatif model can impove communication skills and student learning outcomes in the Biology science subject class VIII.2 SMP Negeri 34 Pekanbaru in the 2019/2020 school year.Key Words: TSTS type cooperatif learning, Communication Skils, Leraning Outcomes